Business Model Canvas as a Conceptual Framework in Building Cooperatives (Case Study on Employees' Cooperative Redriying Bojonegoro) - Sriyadi, (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Cooperatives are business entities that aim to seek social benefits and benefits, so it needs the support of all parties, both directly and indirectly, so that the role of sharia cooperatives in improving the economic welfare of society can be realized with financing products that are very beneficial for cooperatives and for customers. This study aims to analyze the Cooperative business model using the Business Model Canvas. The research method used is descriptive method with a case study approach. While the stages are data collection, data processing and drawing conclusions. The Bojonegoro Kareb Cooperative makes every effort to provide a variety of product services to consumers. Ways to socialize products and make friends are made in the form of WhatsApp groups.